R-CHOP(-like) treatment of diffuse large B-cell lymphoma significantly reduces CT-assessed vertebral bone density: a single center study of 111 patients. Issue 5 (4th May 2017) - Svendsen, Pernille; Shekhrajka, Nitesh; Nielsen, Kasper Lindblad; Vestergaard, Peter; Poulsen, Mette Østergaard; Vistisen, Anders Krog; Munksgaard, Peter Svenssen; Severinsen, Marianne Tang; Jensen, Paw; Johnsen, Hans Erik; Jakobsen, Lasse Hjort; Bøgsted, Martin; et al.
Abstract: Treatment of diffuse large B-cell lymphoma (DLBCL) with R-CHOP(-like) regimens include large cumulative doses of prednisolone. In this retrospective study, we evaluated changes in vertebral bone density (VD) in DLBCL patients by measuring CT-ascertained Hounsfield units (HU) at the L3 level. In total, 111 patients diagnosed from 2007 to 2012 and response assessed following first line treatment were included. Post-treatment VD was significantly reduced to 86% of pretreatment VD on average ( p  < .001). Neither female sex nor high age (>70 years) were significantly associated with greater post-treatment VD reduction. Two years after completing R-CHOP treatment, VD remained significantly lower than baseline VD ( p  < .001). Vertebral compression fractures visualized by CT were found in 16/111 patients (14%) during follow-up. In conclusion, bone mineral density is significantly reduced following R-CHOP(-like) treatment and vertebral compression fractures are common. Glucocorticoid-induced osteoporosis may therefore have impact on survivorship for the large fraction of DLBCL patients with durable remissions.